153k views
3 votes
Which expression is equivalent to

Which expression is equivalent to-example-1
User Debran
by
6.1k points

2 Answers

3 votes

Answer:

Choice B is correct. (1/16)⁻⁴ = (16)⁴

Explanation:

We have given the expression:

(1/16)⁻⁴

We have to find the equivalent expression from the following expressions.

We use the formula (b)⁻¹ = 1/b

(1/16)⁻⁴ = (16 / 1)⁴

(1/16)⁻⁴ = (16)⁴/(1)⁴

(1/16)⁻⁴ = (16)⁴

So, the choice B is correct.

User Paul Whittaker
by
6.2k points
3 votes

Answer:

B) 16^4

Explanation:

Given:
((1)/(16)) ^(-4)

Here we have to use the property a^-1 = 1 / a

Applying the property, we get

=
((16)/(1)) ^(4)

Now we can bring in the power of 4.

= 16^4 / 1^4

= 16^4 / 1

= 16^4

The answer is b) 16^4

Thank you.

User QuadrupleA
by
5.2k points